Pengendalian Persediaan Bahan Baku Untuk Pembuatan Tas dengan Menggunakan Metode Min-Max - Ismail Hafis; Derlini Derlini (Fakultas Teknik Universitas Samudra, 2017)
UD. Rezeki baru is a companies that works in the bag precisely making the field in Menteng VII Medan, North Sumatra. How ever, it has recently encontered a raw material stock problem. Because of it their production rate has decrecored and disadvantages are created due to last minute raw material purchasing. This research is to fine out the amount of raw material at UD. Rezeki baru has been efficient or not when compered using min-max stock method . Based on calculatiing result of raw material inventory in UD. Rezekibaru based on the min-max stock method is not appropriate. Because in some periods there is a shortage of raw materials in the rate of re-ordering on the raw material rope in 2015 amounted to -233.38 meters, lapse of 2016 -233.38 meters and 2016 ruislithing of -1,680 dozen.